Contractile effect of aqueous extract of Artemisia absinthium (ajenjo) against oxytocin in isolated uterus of rats - Osorio-Prudencio, Rosmary Belinda (2022)
Introduction. The use of Artemisia absinthium (wormwood) in labour is widely used in countries in the region; however, there is no enough scientific evidence of its efficacy and safety, which represents a high maternal-fetal risk. Objective. The purpose was to assess the contractile effect of Artemisia absinthium (wormwood) compared to oxytocin in utero isolated from rats. Methods. Eight Holtzman rats were separated into i) Experimental group: Artemisia dose 5, 10, 20, 30, 40, and 50 mg and ii) Control group: oxytocin 10-6 M. The uteruses were mounted in an isolated organ bath, and contractions were recorded for 5 minutes. Results. The frequency of contractions with wormwood 40 and 50 mg were comparable with oxytocin (p>0.05). Likewise, doses of 20 and 30 mg of Artemisia caused significantly longer-lasting contractions than oxytocin. The intensity was found to be comparable with oxytocin at doses of 20, 40, and 50 mg of Artemisia. Conclusion. The aqueous extract of Artemisia absinthium has a contractile effect similar to oxytocin and is dose-dependent in utero isolated from rats.